2021
DOI: 10.3171/2019.12.jns192396
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessments of therapeutic platelet inhibition in endovascular neurosurgery: complication prediction using the VerifyNow P2Y12 assay and thromboelastography with platelet mapping

Abstract: OBJECTIVEInhibition of platelet aggregation is universally used to prevent thromboembolic complications related to stent placement in endovascular neurosurgery, but excessive inhibition potentiates hemorrhagic complications. Previously, the authors demonstrated that two different commercially available measures of adenosine diphosphate (ADP)–dependent platelet inhibition—the VerifyNow P2Y12 clopidogrel assay (measured in platelet reactivity units [PRU]) and maximal am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Studies have shown that for patients with intracranial stent placement, there is no statistically signi cant difference in MA-ADP between the bleeding event group and the non-bleeding event group. They believe that TEG-PM is almost no predictor of bleeding complications in such patients' roles [19]. Another study also pointed out that TEG parameters were not found to be associated with bleeding complications in patients [20].…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that for patients with intracranial stent placement, there is no statistically signi cant difference in MA-ADP between the bleeding event group and the non-bleeding event group. They believe that TEG-PM is almost no predictor of bleeding complications in such patients' roles [19]. Another study also pointed out that TEG parameters were not found to be associated with bleeding complications in patients [20].…”
Section: Discussionmentioning
confidence: 97%
“…VerifyNow quanti es platelet inhibition % induced by antiplatelet therapy. Nevertheless, VerifyNow does not provide information pertaining to other aspects of platelet function, such as clot formation kinetics [19]. PFA-200 assesses primarily primary hemostasis and platelet adhesion, yet it lacks the comprehensive evaluation of clot formation and brinolysis offered by TEG [20].…”
Section: The Comparison Of Platelet Function Testing Methodsmentioning
confidence: 99%
“…Only TEG-PM could not predict thrombotic events or even bleeding complications through neurosurgical procedures [ 173 ]; however, it showed good ability in the prediction of platelet inhibition in comparison to other modalities [ 165 ].…”
Section: Reviewmentioning
confidence: 99%